Estimasi parameter genetik dan peran gen pada uji keturunan full sib kayu putih di Gunung Kidul - Kartikawati, Noor Khomsah; Naiem, Mohammad; Hardiyanto, Eko Bhakti (BBPPBPTH, 2013)
Controlled pollination technique could be applied to generate gene recombinant from families in progeny test and to estimate genetic parameters. The early step in evaluation of controlled pollination is to estimate general combining ability and specific combining ability. the objectives of this research were to estimate generic parameters on full sib progeny test of melaleuca cajuputi subsp cajuputi cajuput and to identify gene action controlling growth and oil traits. The research was conducted on full sib progeny test at Gunungkidul established in an incomplete block Design with six treeplots and eight replications. Tree height and diameter stem growth were observed at seven years old. Oil yield and cineol content were examined using gas chromatography. Analysis of variance and genetic parameter were calculated for all measured variables. The result showed that individual heretabilities on growth traits (hi2 of stem diameter = 0,34 and tree height = 0,01, respectively) were lower than on oil traiths (hi2 of oil yield =0,6 and cineole = 0,4 respectively). This indicated that oil traits tend to genetically controlled. Analysis of variances on general combining ability (GCA) and Specific Combining Ability (SCA) effects from a serries of 15 sets of 5x5 half-diallel mating experiments showed that all traits (height, diameter, oil and 1,8 cineole yields) were controlled by non-aditive genes. Consequently, controlled pollination of selected plus trees should be carried out until heterosis of improved progenies could be found.